2013
DOI: 10.1007/s13158-013-0081-6
|View full text |Cite
|
Sign up to set email alerts
|

Intuitive and Informal Knowledge in Preschoolers’ Development of Probabilistic Thinking

Abstract: Abstract:Preschoolers develop a wide range of mathematical informal knowledge and intuitive thinking before they enter formal, goal-oriented education. In their everyday activities young children get engaged with situations that enhance them to develop skills, concepts, strategies, representations, attitudes, constructs and operations concerning a wide range of mathematical notions. Recently there is scientific interest in linking children's informal and formal knowledge in order to provide them with opportuni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 19 publications
1
10
0
2
Order By: Relevance
“…Risk-taking is interconnected with aspects of cognitive, social, emotional and biological development (Boyer, 2006). Through diverse contexts and play situations, children have been found able to reason and face feasibilities, estimate odds and therefore make probability judgments, and deal both semantically and conceptually with the evaluation of future events (Nikiforidou et al, 2013). Moreover, children as young as four can understand and rationalize safety and non-safety matters.…”
Section: Risk and Young Childrenmentioning
confidence: 99%
See 1 more Smart Citation
“…Risk-taking is interconnected with aspects of cognitive, social, emotional and biological development (Boyer, 2006). Through diverse contexts and play situations, children have been found able to reason and face feasibilities, estimate odds and therefore make probability judgments, and deal both semantically and conceptually with the evaluation of future events (Nikiforidou et al, 2013). Moreover, children as young as four can understand and rationalize safety and non-safety matters.…”
Section: Risk and Young Childrenmentioning
confidence: 99%
“…Studies have shown that children as young as four demonstrate an understanding of probabilities and expected value, adjust preferences based on probabilities, indicate notions of probabilistic thinking, and possess specific concepts and skills associated with probabilistic reasoning like causal strength, future reasoning and linguistic capacity connected to risk (e.g. Nikiforidou et al, 2013; Nikiforidou, 2017). Therefore, risk literacy can be connected to probabilistic tasks with dice, cards, and guessing and prediction games in exploring possible future outcomes.…”
Section: Risk Literacy As Part Of Ecementioning
confidence: 99%
“…En sus actividades cotidianas, los niños pequeños participan en situaciones que promueven el desarrollo de habilidades, percepciones, estrategias, representaciones, actitudes, construcciones y operaciones relacionadas con una amplia gama de conceptos matemáticos (Nikiforidou, Pange, & Chadjipadelis, 2013). En esta línea, Ginsburg et al (2008) mencionan que los investigadores en los últimos años han acumulado evidencias que demuestran que, desde el nacimiento hasta los cinco años de edad, los niños desarrollan una matemática cotidiana (incluyendo ideas informales de más y menos, adición, sustracción, forma, tamaño, localización, patrones, posición, etc.)…”
Section: Matemática Informal En Los Niñosunclassified
“…Intuitions may emerge in both formal and informal contexts, but in the case of early years in terms of time intuitive thinking is mainly associated with informal knowledge. Under this perspective, young children are expected to estimate odds and unpredictability and therefore make probability judgments at a certain level, prior to formal learning (Nikiforidou, Pange & Chadjipadelis, 2013).…”
Section: Introductionmentioning
confidence: 99%